Highway Lane Rental Requirement Compromises Blast Site Safety and Security - Harry L. Siebert (International Society of Explosives Engineers, 1997)
A major Arizona highway project is jeopardizing site safety and security because of the lane rental policy. One million cubic yards of rock must be fragmented to provide two additional lanes parallel to the existing roadway. Traffic is stopped during blasting operations.